Significance of 4D printing for dentistry: Materials, process, and potentials - Mohd Javaid; Abid Haleem; Ravi Pratap Singh; Shanay Rab; Rajiv Suman; Lalit Kumar (Elsevier, 2022)
Every industry need helps to modify its working style quickly with the improvement of existing technology. New developing technologies improve production speed, reduce industrial process costs, etc. Technical specialists carry out continuous research and development to increase efficiency. A significant advance in 4D printing over 3D Printing is its capacity to alter shape over time because external elements such as pressure, air, heat, water, etc., use controlled impact. 4D Printing has one "D'' instead of 3D Printing, and the fourth aspect is time. Therefore, its capacity to alter shape over time is a significant advancement of 4D printing over 3D printing technologies. It is evident that 4D printing will be of tremendous value to manufacturers regarding features and advances in dentistry. Its applications cover medical modelling, surgical guides manufacture, prosthodontics, dentistry, orthodontics, implantology, and dentistry instruments. This paper is brief about 4D printing and its printing of smart materials through 4D printing. Process workflow and Bio-Oriented 4D printable smart materials for dentistry are presented diagrammatically. Further, the paper identifies and discusses the significant potential of 4D printing for dentistry. 4D printing is an innovative technology that uses the inputs from smart materials, and the 3D printed item becomes another structure via the impact of external energy sources such as temperature, light, or other environmental stimuli. The objective is to integrate technology and design to create self-assembly and programmable material technologies that better design, production, and performance.